2021
DOI: 10.3390/jlpea11030029
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Non-Von Neumann Computing Architecture Supporting Multiple Computing Paradigms for Logic and Binarized Neural Networks

Abstract: Different in-memory computing paradigms enabled by emerging non-volatile memory technologies are promising solutions for the development of ultra-low-power hardware for edge computing. Among these, SIMPLY, a smart logic-in-memory architecture, provides high reconfigurability and enables the in-memory computation of both logic operations and binarized neural networks (BNNs) inference. However, operation-specific hardware accelerators can result in better performance for a particular task, such as the analog com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Also, simulations confirmed that by delivering only small read voltages to the RRAM devices, the effect of variability is virtually solved. In addition, V COND is no more required, and since V SET is applied only when P and Q are zero, in three out of four cases of the truth table the energy consumption is greatly reduced with respect to the stateful implementation, as discussed in [28]. Additional energy can be saved using the same approach on the FALSE operation, thus splitting the operation into a read step followed by a conditional V FALSE pulse.…”
Section: The Smart Materials Implication Logicmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, simulations confirmed that by delivering only small read voltages to the RRAM devices, the effect of variability is virtually solved. In addition, V COND is no more required, and since V SET is applied only when P and Q are zero, in three out of four cases of the truth table the energy consumption is greatly reduced with respect to the stateful implementation, as discussed in [28]. Additional energy can be saved using the same approach on the FALSE operation, thus splitting the operation into a read step followed by a conditional V FALSE pulse.…”
Section: The Smart Materials Implication Logicmentioning
confidence: 99%
“…Since only a sufficient read margin needs to be ensured, this approach is intrinsically more reliable than the stateful one. In fact, circuit simulations performed in [26,28,29] with the compact model, including the effect of variability and RTN showed that a sufficiently large read margin is easily obtained by tuning the read voltage and V FALSE (i.e., higher HRS leads to larger memory windows). Also, simulations confirmed that by delivering only small read voltages to the RRAM devices, the effect of variability is virtually solved.…”
Section: The Smart Materials Implication Logicmentioning
confidence: 99%
See 2 more Smart Citations
“…The bitwise MAC operation enables extensive applicability to resource-constrained platforms, such as edge devices and mobile processors, promising a considerable reduction in memory (approximately 32 ×) and computation (approximately 2 ×) requirements compared with other neural networks 6 10 . Furthermore, it is still difficult for emerging synaptic devices to fully implement analog neural networks (analog input and analog weight) with nonlinear conductance changes and device variations 1 4 , 11 13 . However, digital synaptic devices are suitable for implementing BNNs because of their binarized weights 13 16 .…”
Section: Introductionmentioning
confidence: 99%